Atlas of Endoscopic Neurosurgery of the Third Ventricle : Basic Principles for Ventricular Approaches and Essential Intraoperative Anatomy - Dezena, Roberto Alexandre (Springer International Publishing : Imprint: Springer, 2017)
This book describes in practical terms the endoscopic neurosurgery of the third ventricle and surrounding structures, emphasizing aspects of intraoperative endoscopic anatomy and ventricular approaches for main diseases, complemented by CT / MRI images. It is divided in two parts: Part I describes the evolution of the description of the ventricular system and traditional ventricular anatomy, besides the endoscopic neurosurgery evolution and current concepts, with images and schematic drawings, while Part II presents a collection of intraoperative images of endoscopic procedures, focusing in anatomy and main pathologies, complemented by schemes of the surgical approaches and CT / MRI images. The Atlas of Endoscopic Neurosurgery of the Third Ventricle offers a revealing guide to the subject, addressing the needs of medical students, neuroscientists, neurologists and especially neurosurgeons. .
Keywords: Medicine.; Neurosciences.; Human anatomy.; Neurology.; Neurosurgery.; Minimally invasive surgery.; elektronické knihy; electronic books